Why smallholders stop engaging in forest activities: The role of in-migration in livelihood transitions in forested landscapes of southwestern Ethiopia - Juliane Groth; Ralf Seppelt; Patrick Sakdapolrak; Feyera Senbeta; Kathleen Hermans (Ecology & Society, 2023)
Forest decline and degradation are particularly high in the tropics and pose a risk to those who depend on forest resources. The in-migration of smallholders to forest frontiers can fuel transitions of livelihoods and land and resource use. However, the conditions under which in-migration contributes to such transitions remain poorly understood. With this study, we aim to investigate the influence of in-migration, together with other non-demographic factors, on the livelihoods of local and migrant communities. As a case study, we chose the Guraferda district, a hotspot of rural in-migration and forest loss in southwest Ethiopia, where the forest-based local population experienced a rapid transition to agriculture-based livelihoods. We used 224 household surveys in three different kebeles (smallest administrative unit in Ethiopia) and applied descriptive and analytical statistics to understand how and why the forest activities of local and migrant groups have changed since a major resettlement program was launched in 2003. The findings were contextualized by local expert knowledge to assess forest loss and the role of in-migration in livelihood transitions and deforestation. Forest cover in Guraferda declined partially because of the in-migration of smallholders from agricultural-based systems, and insecure land tenure, but also considerably because of the expansion of commercial agriculture. With the decline in forest, the local population adopted migrants' agricultural practices, a trend further encouraged by agricultural policies and barriers to participation in forest management for locals. Our study challenges simplified assumptions in in-migration–deforestation debates by showing that governmental policies, land tenure, and natural-resource access are mediating the impact of migration on livelihood transitions and deforestation. We conclude that securing land tenure and equal access to natural resources for frontier residents and promoting a mix of agricultural and forest livelihood activities can reduce adverse impacts in in-migration areas.
Keywords: 320; Africa; in-migration; livelihood transition; natural-resource degradation; random-forest regression